2014
DOI: 10.1002/star.201400164
|View full text |Cite
|
Sign up to set email alerts
|

Edible films based on native and phosphated 80:20 waxy:normal corn starch

Abstract: Edible films based on 80:20 waxy:normal corn starch were evaluated for their potential use in the food industry. Two types of film were prepared by the casting method: The first from native corn starch and the second from starch modified with glycerol. The influence of this chemical modification on the physicochemical and mechanical properties of both the starch and films was investigated. The phosphation of the base material improved the interaction between the plasticizer and the modified starch. This was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…1 c and d)have 256 a slight increase in grain size. Similar results have been reported by Gutiérrez et al[61] 257 in phosphated starches of cassava and dark-cush-cush yam. Additionally, in theFigure 2581d was observed that the crystallinity of the starch is maintained, since the cross of…”
supporting
confidence: 91%
See 2 more Smart Citations
“…1 c and d)have 256 a slight increase in grain size. Similar results have been reported by Gutiérrez et al[61] 257 in phosphated starches of cassava and dark-cush-cush yam. Additionally, in theFigure 2581d was observed that the crystallinity of the starch is maintained, since the cross of…”
supporting
confidence: 91%
“…Similar results 212 were reported by Gutiérrez The crude protein content was relatively low in the native and modified plantain flours, 215 between 1.00-2.62% (Table 1). The reduction of the 50% of crude protein content was 216 recorded for the modified plantain flour, possibly this has been due to the leaching of 217 the proteins during the modification of the flour [61]. So the same, the beet flour had a 218 protein content (10.3%), an order of magnitude greater than plantain flours [70].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The coarse‐grained GPFF microstructure could be responsible for the higher rate of water loss. Gutierrez et al observed that the addition of waxy starch confers thermal stability to glycerol‐based films, maybe by the strong binding of glycerol to amylopectin chains. Similar effects were observed by Wokadala et al for PLA/starch films.…”
Section: Resultsmentioning
confidence: 99%
“…Among starches, cassava, corn, and wheat starches have been recently proposed for the formulation of edible films thanks to their availability and relatively low price. Starch is normally used in mixtures with different biomaterials, such as soybean protein concentrates, native and modified cush‐cush yam and cassava starches, wax and normal starches, wheat starch and whey‐protein isolates, wheat starch solution and rapeseed oil, and cassava starch, glycerol, carnauba wax and stearic acid …”
Section: Edible Active Matricesmentioning
confidence: 99%